Zen and the art of mixing - Mixerman (Milwaukee, WI : Hal Leonard, 2014)
"In his first book, The Daily Adventures of Mixerman, the author detailed the frustrating and often hilarious goings on during the process of recording a major-label band. Musicians, engineers, and producers laughed and cried at the crazy goings-on they'd never imagined or recognized all too well. Now Mixerman turns his razor-sharp gaze to the art of mixing and gives followers and the uninitiated reason to hope, if not for logic and civility in the recording studio then at least for a good sounding record. With a firm commitment to art over technology and to maintaining a grasp of each, Mixerman outlines his own approach to recording success, based on his years mixing records in all genres of music for all kinds of artists, often under trying circumstances. As he states in his introduction to the new volume, "Even if you're not a professional mixer, even if you're a musician trying to mix your own work or a studio owner in a smaller market, you have your own set of pressures to deal with while you're mixing. Regardless of what those pressures are, it's important to identify and recognize them, if for no other reason than so you can learn to completely ignore them". That's where the Zen comes in. -- Publisher description.
(Technical Reference). In his first book, The Daily Adventures of Mixerman, the author detailed the frustrating and often hilarious goings-on during the process of recording a major-label band. Musicians, engineers, and producers laughed and cried at the crazy goings-on they'd never imagined or recognized all too well.
Introduction -- 1. The mix and the mixer -- 2. Arrangement and focus -- 3. The mechanics -- 4. Gear -- 5. Dealing with clients -- 6. Mastering -- 7. Thinking outside the box.
Includes bibliographical references.
Keywords: Mixerman; Sound engineers -- United States; Popular music -- Production and direction; Sound -- Recording and reproducing; Sound studios